2019
DOI: 10.1371/journal.pone.0227063
|View full text |Cite
|
Sign up to set email alerts
|

The delay of motherhood: Reasons, determinants, time used to achieve pregnancy, and maternal anxiety level

Abstract: BackgroundFertility in recent decades in European countries such as Norway, Spain or United Kingdom has declined, while in others such as Portugal, it has remained relatively constant, and in others such as Germany fertility rated have risen. The determinants of this change in reproductive pattern can be explained by the cultural, social, and economic changes that took place in our society. Objective: to identify the principal reasons and independent determinants associated with the postponement of motherhood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 25 publications
(26 reference statements)
1
21
0
Order By: Relevance
“…In particular, long‐acting reversible contraceptives use has decreased the risk of unplanned pregnancies 4,5 . There are also women in their late 30s and 40s underestimating their fertility, resulting in unplanned pregnancies among those who are not using any contraception or who are using less effective contraceptive methods 1 …”
Section: Introductionmentioning
confidence: 99%
“…In particular, long‐acting reversible contraceptives use has decreased the risk of unplanned pregnancies 4,5 . There are also women in their late 30s and 40s underestimating their fertility, resulting in unplanned pregnancies among those who are not using any contraception or who are using less effective contraceptive methods 1 …”
Section: Introductionmentioning
confidence: 99%
“…Infertility is defined as the failure to achieve a clinical pregnancy after at least 12 months of regular, unprotected sexual intercourse (Zegers-Hochschild et al, 2009). This condition is becoming increasingly common, likely in part due to the modern trend to pursue educational goals and economic stability prior to starting a family, therefore delaying pregnancy until older age (Molina- García et al, 2019) Current literature has suggested that parenthood is considered to be central to the life plan of most adults (Boivin et al, 2018). Both men and women can feel an intense and profound desire for parenthood, indicating an emotional engagement acting as a driving force for patients to seek treatment for infertility (Hadley and Hanley, 2011;Langher et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomal aneuploidy in human oocytes is not a rare event, exemplified by a 20% incidence in 32‐year‐old women that further increases with age, reaching 60%–80% in women aged 42 (Capalbo, Hoffmann, Cimadomo, Maria Ubaldi, & Rienzi, 2017; Jones & Lane, 2013; Kuliev, Zlatopolsky, Kirillova, Spivakova, & Cieslak Janzen, 2011). This so called “age‐related aneuploidy” in oocytes has long been a focus in the study of human reproduction, as women in economically advanced societies are trending to delay their pregnancies (Molina‐García et al, 2019). However, we are still far from fully understanding the mechanisms underlying this phenomenon.…”
Section: Introductionmentioning
confidence: 99%